Cover Feature: Water Electrolysis in Saturated Phosphate Buffer at Neutral pH (ChemSusChem 22/2020). Issue 22 (27th October 2020) - Naito, Takahiro; Shinagawa, Tatsuya; Nishimoto, Takeshi; Takanabe, Kazuhiro
Abstract : The Cover Feature shows large mass‐transport flux made possible by the highly concentrated buffer solution at elevated temperatures for water splitting. The demonstrated electrolysis performance in the solution was comparable to that of the conventional electrolyzer operating at extreme pH levels, casting a new proposal that the highly concentrated buffer solutions can be regarded as an alternative environment for water electrolysis. More information can be found in the Full Paper by T. Naito et al .